2013
DOI: 10.1111/trf.12044
|View full text |Cite
|
Sign up to set email alerts
|

Fresh whole blood use by forward surgical teams in Afghanistan is associated with improved survival compared to component therapy without platelets

Abstract: The use of FWB in austere combat environments appears to be safe and is independently associated with improved survival to discharge when compared with resuscitation with RBCs and FFP alone. Mortality was similar for patients transfused uncrossmatched Type O compared with ABO type-specific FWB in an austere setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
162
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(179 citation statements)
references
References 33 publications
3
162
1
4
Order By: Relevance
“…28,29 We found that patients who received transfusion of blood components were 3 times more likely to die than were patients who received whole blood after trauma, regardless of injury severity (OR, 3.164; 95% CI, 1.314-7.618). 30 Only recently have investigators performed a randomized controlled trial to compare transfusion of fresh whole blood with transfusion of blood components.…”
Section: Transfusion Of Blood Components and Potential Consequencesmentioning
confidence: 90%
“…28,29 We found that patients who received transfusion of blood components were 3 times more likely to die than were patients who received whole blood after trauma, regardless of injury severity (OR, 3.164; 95% CI, 1.314-7.618). 30 Only recently have investigators performed a randomized controlled trial to compare transfusion of fresh whole blood with transfusion of blood components.…”
Section: Transfusion Of Blood Components and Potential Consequencesmentioning
confidence: 90%
“…[4] FWB is more concentrated than blood products prepared with a 1:1:1 ratio of RBCs, frozen plasma, and platelets, and is the only functional alternative that includes all fractions. Nessen et al [5] evaluated the therapeutic role of additional FWB treatment in patients who required platelet replacement after having received RBCs and FFP. It was concluded that administration of FWB increased survival.…”
Section: Discussionmentioning
confidence: 99%
“…Точно так же, Nessen и др. нашли, что трансфузия СЦК была независимым предиктором выживания у раненных в бою (~ 90%-ое сокращение вероятности летальности), по сравнению с теми раненными, которые неоднократно получали компоненты крови, несмотря на более высокую оценку по ISS, и более низкое АД [50]. После поправки на возраст, пол, и на действие другого средства, те пациенты, которым переливали компо-ненты крови, в 3.2 раза более вероятно умрут при сравнении с пациент ами, которые получили СЦК (OR 3.164, 95%-ый CI 1.314 -7.618, p = 0.010) по данным Jones и др.…”
Section: влияние трансфузий сцк или кк на смертностьunclassified
“…У раненных пациентов, которые получали СЦК, была увеличена в два раза вероятность 30-дневного выживания по сравнению с паци-ент ами, которые получали компоненты крови (OR 2.15, 95% CI 1.21-3.8, p = 0.016). Кроме того, в нескольких рет ро спек-тивных исследованиях показано ассоциа-цию с улучшенным выживанием, при использовании СЦК у больных, которым применяли damage -конт роль в го спи-талях [50].…”
Section: Review P P P a A A I I I N N N A A A N N N A A A E E Eunclassified